Volatile Compound Screening Using Hs-Spme-Gc/Ms on Saccharomyces Eubayanus Strains Under Low-Temperature Pilsner Wort Fermentation - Salazar-Gonzalez, R; Santander-Meyer, R; Cubillos-Riffo, F; Villarreal-Diaz, P; Urbina, K (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The recent isolation of the yeast Saccharomyces eubayanus has opened new avenues in the brewing industry. Recent studies characterized the production of volatile compounds in a handful set of isolates, utilizing a limited set of internal standards, representing insuffcient evidence into the ability of the species to produce new and diverse aromas in beer. Using Headspace solid-phase microextraction followed by gas chromatography-mass spectrometry (HS-SPME-GC-MS), we characterized for the first time the production of volatile compounds in 10 wild strains under fermentative brewing conditions and compared them to a commercial lager yeast. S. eubayanus produces a higher number of volatile compounds compared to lager yeast, including acetate and ethyl esters, together with higher alcohols and phenols. Many of the compounds identified in S. eubayanus are related to fruit and floral flavors, which were absent in the commercial lager yeast ferment. Interestingly, we found a significant strain × temperature interaction, in terms of the profiles of volatile compounds, where some strains produced significantly greater levels of esters and higher alcohols. In contrast, other isolates preferentially yielded phenols, depending on the fermentation temperature. This work demonstrates the profound fermentation product differences between different S. eubayanus strains, highlighting the enormous potential of this yeast to produce new styles of lager beers. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: yeast; volatile compounds; S. eubayanus; beer; lager